Gerhardtite as a Precursor to an Efficient CO-to-Acetate Electroreduction Catalyst - Wu, Zhi-Zheng; Zhang, Xiao-Long; Yang, Peng-Peng; Niu, Zhuang-Zhuang; Gao, Fei-Yue; Zhang, Yu-Cai; Chi, Li-Ping; Sun, Shu-Ping; DuanMu, Jing-Wen; Lu, Pu-Gan; Li, Ye-Cheng; Gao, Min-Rui (Journal of the American Chemical Society, 2023)
Carbon–carbon coupling electrochemistry on a conventional copper (Cu) catalyst still undergoes low selectivity among many different multicarbon (C2+) chemicals, posing a grand challenge to achieve a single C2+ product. Here, we demonstrate a laser irradiation synthesis of a gerhardtite mineral, Cu2(OH)3NO3, as a catalyst precursor to make a Cu catalyst with abundant stacking faults under reducing conditions. Such structural perturbation modulates electronic microenvironments of Cu, leading to improved d-electron back-donation to the antibonding orbital of *CO intermediates and thus strengthening *CO adsorption. With increased *CO coverage on the defect-rich Cu, we report an acetate selectivity of 56 ± 2% (compared to 31 ± 1% for conventional Cu) and a partial current density of 222 ± 7 mA per square centimeter in CO electroreduction. When run at 400 mA per square centimeter for 40 h in a flow reactor, this catalyst produces 68.3 mmol of acetate throughout. This work highlights the value of a Cu-containing mineral phase in accessing suitable structures for improved selectivity to a single desired C2+ product.